Effect of Ashi Point Pricking and Cupping Combined with Quadriceps Femoris Function Exercise on the Clinical Curative Effect of Knee Osteoarthritis - Zhiqiang HUANG; Yu LIU; Zhaoyuan SU; Jiafu SU; Qiang WU (康复学报)
Objective:To observe the clinical effect of Ashi pricking and cupping combined quadriceps function exercise in the treatment of knee osteoarthritis.Methods:A total of 98 patients with knee osteoarthritis(KOA)who met the diagnostic criteria and inclusion criteria were selected, the patients with KOA were randomly divided into drug group and comprehensive group, each group was treated with a total of 49 cases. The drug group was treated with drug therapy and quadriceps femoris function exercise, namely diclofenac sodium sustained release tablets 75 mg, 1 time/day, omeprazole 20 mg, 1 time/day; the comprehensive group was treated by Ashi pricking blood with cupping combined quadriceps femoris function exercise therapy. The changes of the Western Ontario and McMaster Universities Osteoarthritis Index(WOMAC)score, range of motion of joints, levels of inflammatory factors and clinical efficacy were compared between the two groups before and after treatment.Results:The clinical effect of the comprehensive group was better than the drug group(P<0.05).WOMAC score(pain, daily activities, joint stiffness, comprehensive score)of the two groups after treatment was significantly lower than that before treatment(P<0.05).After treatment, WOMAC score of the comprehensive group was significantly lower than that of the drug group(P<0.05);joint range of motion of the two groups was larger than that before treatment(P<0.05), and joint range of motion of the comprehensive group was larger than that of the drug group(P<0.05);tumor necrosis factor alpha(TNF-α)and interleukin 1(IL-1)levels of the two groups were lower than those before treatment(P<0.05), TNF-α and IL-1 of the comprehensive group were significantly lower than those of the drug group(P<0.05).Conclusion:The method of Ashi point pricking and cupping combined with quadriceps femoris functional exercise can relieve joint pain, increase joint range of motion, reduce the inflammatory index of joint, and then improve the function of knee joint of KOA.